1998
DOI: 10.1002/aic.690440225
|View full text |Cite
|
Sign up to set email alerts
|

Measured and modeled superficial flow profiles in packed beds with liquid flow

Abstract: Packed bed chemical reactors, adsorbers and heat exchangers are simulated by partial differential equations derived from energy and species balances. To solve these equations, an assumption has to be made with respect to the average flow distribution (superficial flow profile) over the cross section of the tubular packed bed. Commonly plug flow is assumed, although the real flow distributions exhibit near-wall flow maxima due to a higher porosity and the no-slip condition at the wall. To our knowledge, Saunder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
167
0
17

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(211 citation statements)
references
References 20 publications
17
167
0
17
Order By: Relevance
“…10 comparison with data of (Zhang et al, 2006) is shown for minimum and maximum density packing of cylinders (E1 and E2, respectively). Quantitative comparison with experimental data of (Giese et al, 1998) reveals good agreement near the container wall but, as the spatial scale of the oscillations is a little larger in the numerical simulation, discrepancies arise in the bed interior (Fig. 11).…”
Section: Radial Porosity Profilementioning
confidence: 79%
See 1 more Smart Citation
“…10 comparison with data of (Zhang et al, 2006) is shown for minimum and maximum density packing of cylinders (E1 and E2, respectively). Quantitative comparison with experimental data of (Giese et al, 1998) reveals good agreement near the container wall but, as the spatial scale of the oscillations is a little larger in the numerical simulation, discrepancies arise in the bed interior (Fig. 11).…”
Section: Radial Porosity Profilementioning
confidence: 79%
“…11. Radial porosity profile -quantitative comparison with experimental data of Giese et al (1998) 4. CONCLUSIONS…”
Section: E1 E2mentioning
confidence: 99%
“…Thus the model cannot predict the velocity maximum in the vicinity of the wall observed experimentally for those reactors [56]. An averaged velocity with a radially varying axial component can be provided by a further modification of the momentum balance [56][57][58] as an improvement of the classical model. The reader is referred to the textbook by Keil [54] and references therein.…”
Section: Modeling Gaseous Transport In Porous Catalystsmentioning
confidence: 99%
“…An averaged velocity with a radial varying axial component can be provided by a further modification of the momentum balance [76][77][78] as improvement of the classical model.…”
Section: Momentum and Energy Equations For Porous Mediamentioning
confidence: 99%